Pheochromocytoma – clinical manifestations, diagnosis and current perioperative management - Dragos Radu Marcu; Ovidiu Gabriel Bratu; Ana Maria Alexandra Stanescu; Anca Pantea Stoian; Mihnea Alexandru Gaman; Camelia Cristina Diaconu (Journal of Mind and Medical Sciences)
Pheochromocytoma is a neuroendocrine tumor characterized by the excessive production of catecholamines (epinephrine, norepinephrine, and dopamine). The diagnosis is suspected due to hypertensive paroxysms, associated with vegetative phenomena, due to the catecholaminergic hypersecretion. Diagnosis involves biochemical tests that reveal elevated levels of catecholamine metabolites (metanephrine and normetanephrine). Functional imaging, such as 123I-metaiodobenzylguanidine scintigraphy (123I-MIBG), has increased specificity in identifying the catecholamine-producing tumor and its metastases. The gold-standard treatment for patients with pheochromocytoma is represented by the surgical removal of the tumor. Before surgical resection, it is important to optimize blood pressure and intravascular volume in order to avoid negative hemodynamic events.